Trends in the sequence of first alcohol, cannabis and cigarette use in Australia, 2001–2016. (1st February 2020) - Livingston, Michael; Holmes, John; Oldham, Melissa; Vashishtha, Rakhi; Pennay, Amy
Highlights: The age of initiation for alcohol, tobacco and cannabis increased markedly in Australia recently. Cigarettes are no longer the first substance used by most people using multiple substances. Alcohol use still precedes cannabis use for most young Australians who use both Abstract: Background: Recent analyses of data from the US found that young people were increasingly engaging in cannabis use before alcohol and cigarettes. These shifts are important for public health, but it is not clear whether such trends extend beyond the US. The aim of this study is to examine whether and how the age and sequencing of initiation into alcohol, cannabis and cigarette use has changed in Australia since the early 2000s. Methods: Data came from six waves of the Australian National Drug Strategy Household Survey, spanning 2001–2016. We used data from 18 to 21 year-olds (n = 6849) and examined trends in the age at first use for each of the three substances plus any changes in the order of initiation. Results: The mean age of initiation increased steadily for all three substances (e.g. from 14.9 in 2001 to 16.4 in 2016 for alcohol), while the prevalence of any use declined. There were some changes in ordering of use. For example, in 2001, 62 % of respondents who used both cigarettes and cannabis had first used cigarettes at an earlier age than cannabis, compared with 41 % in 2016. Young people who used both alcohol and cannabis remained more likely to try alcohol before cannabis across the study period. Conclusions: Our results partly replicated US findings, with differences potentially reflecting the substantially different environment around these substances in the US compared to Australia. The age of initiation for alcohol, cigarette and cannabis use in Australia has increased sharply over the past 15 years.